Spatial Barriers and the Tendency of the Utilization of Mediated Citizenship by Villagers in Accessing Public Services - Hidayat, Rahmad; Akhyar, Akhyar; Sauki, Muhammad (HK-Publishing, 2021)
AbstractThis paper aims to discuss the dynamic intersection between the spatial barriers and the tendency of the utilization of